Attitudes of 4th year Teacher towards Teaching and the Relationship to their Achievement (Degree) - Rasheed, Raâ€™eda Mohammad (European Scientific Journal, ESJ, 2016)
This study addresses the attitudes of 4th year teacherâ€“students of mathematics and Special Education Specializations at Jubail College of Education towards teaching, and the relationship to their achievement (degree) in the specialized mathematical courses of educational preparation. The theoretical importance of studying the attitudes of teacher-students of mathematics and Special Education for students with mathematics learning abilities student-teachersâ€˜ (students studying in College of Education) attitudes stems from its importance in future planning of teaching at the Kingdom of Saudi Arabia (KSA) level. In addition, it is an influential factor in broadening studentsâ€™ admission to the College of Education. Also, the stage addressed by this study is critical because it is the final stage of the studentsâ€™ study. These students are about to graduate and head for field and practical application where the specialized educational courses appear to be mostly beneficial. The study sample that was randomly selected consisted of the (28) Mathematics Departmentâ€™s female students who were studying â€œMathematics Methodologyâ€ at the 6th level, and â€œDesign and Develop Mathematics Lessonsâ€ at the 7th level of the scholastic year 1435/1436h.The sample also consisted of (45) Special Education female students studying â€œMathematics for Special Education Teachersâ€ at the 7th level of the scholastic year 1435/1436.The study instrument consisted of â€œThe Attitude towards Teaching Scaleâ€, which was sought from a study conducted by the researcher Ahmad Al-Hussein, with the title â€œAttitudes of Imam Mohammad bin Saud Islamic University Students Towards Teachingâ€. The instrument consisted of (32) paragraphs with a 5-point rating scale (completely agree, agree, do not know, disagree, strongly disagree), which was extracted from the peer-reviewed scientific periodical of Education and Psychology Message, issued by Saudi Educational and Psychological Association, No.(35) of the year (2010).The study adopted the reviewerâ€™s validity Chronbach Alpha for internal consistency to calculate the reliability of the study instrument which was (0.73) for the study instrument scale used to measure the attitudes towards teaching. This value is adequate for the research purposes of the study. Statistical treatment was concerned with calculating the means and standard deviation, Pearson correlation coefficient between the means of the study sample attitudes towards teaching and their achievement in the courses of specialized mathematical courses of educational preparation. Regression analysis was also calculated, in addition to the ANOVA variance, to identify the relation of attitudes common among the study sample towards teaching as an independent variable, and their degree in the specialized mathematical courses of educational preparation as a dependent variable. The study concluded that there is a weak attitudinal correlative relationship, towards teaching with the degrees of students from the Mathematics and Special Education Department, according to the statistical treatments, in specialized teaching methods of mathematics/education courses. The weakness of such correlation is ascribed to the weakness of some of studentsâ€™ attitudes as shown from their response to the paragraphs of the questionnaire. This requires fostering and developing studentsâ€™ attitudes towards teaching in a way that helps in raising their achievement at the specialized mathematics/education courses. The study recommended that educators at the Colleges of Education should consider fostering attitudes towards teaching, because it raises studentsâ€™ achievement at the educational courses in particular, and academic courses for the students of the Colleges of Education in general.